2016
DOI: 10.1039/c6tc01891b
|View full text |Cite
|
Sign up to set email alerts
|

Water dispersed fluorescent organic aggregates for the picomolar detection of ClO4in water, soil and blood serum and the attogram detection of ClO4in the solid state by a contact mode method

Abstract: An aggregation–disaggregation based molecular probe allows the detection of 10 pM ClO4−in solution and 6 × 10−18g cm−2ClO4−in the solid state by a contact mode method with a selectivity of ∼10 000 over other inorganic anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The turbidity was due to the formation of aggregates, as observed by dynamic light scattering (DLS) experiments (Figure S1 in the Supporting Information). It was reported that the aggregates were used as sensors and catalysts [57–61] . High‐resolution images of the aggregates were recorded by using the atomic force microscopy (AFM) technique to investigate the sizes and morphologies of the aggregates (Figure 3 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…The turbidity was due to the formation of aggregates, as observed by dynamic light scattering (DLS) experiments (Figure S1 in the Supporting Information). It was reported that the aggregates were used as sensors and catalysts [57–61] . High‐resolution images of the aggregates were recorded by using the atomic force microscopy (AFM) technique to investigate the sizes and morphologies of the aggregates (Figure 3 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…The rate of radiative decay of the excited state decreases as the concentration of ATP increases in solution, whereas the lifetime of the excited state increases. This transformation is due to the formation of aggregates where properties of the excited state are different and lead to an increased lifetime, 79 whereas a decreasing radiative decay constant is attributed to quenching of the excimer emission. We observed a minor change in the nonradiative decay constant upon addition of ATP to the R3 solution.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…23,24 Currently, due to the weak coordination behavior of perchlorate, 25 efforts to develop its optical probes have met limited success. [26][27][28] Although several luminescent turn-on perchlorate probes have been reported, such as the pyridinium-functionalized tetraphenylethene compound 27 and ionic iridium(III) complex, 26 none exhibit simultaneously colorimetric response. The conventional construction by integrating a chromophore onto the luminophore is poorly feasible for the perchlorate dual-mode sensor, owing to the extremely limited number of perchlorate chromophore (methylene blue is the most oen used, but with a low-contrast color change from blue to purple).…”
Section: Introductionmentioning
confidence: 99%